5.0k views
3 votes
Q/13 + 11 = 13 Please show me a step by step

2 Answers

4 votes

Answer:

26

Explanation:

Solve for q:

q/13 + 11 = 13

Put each term in q/13 + 11 over the common denominator 13: q/13 + 11 = q/13 + 143/13:

q/13 + 143/13 = 13

q/13 + 143/13 = (q + 143)/13:

(q + 143)/13 = 13

Multiply both sides of (q + 143)/13 = 13 by 13:

(13 (q + 143))/13 = 13×13

(13 (q + 143))/13 = 13/13×(q + 143) = q + 143:

q + 143 = 13×13

13×13 = 169:

q + 143 = 169

Subtract 143 from both sides:

q + (143 - 143) = 169 - 143

143 - 143 = 0:

q = 169 - 143

169 - 143 = 26:

Answer: |

| q = 26

User Gerald Eersteling
by
5.0k points
4 votes

Answer:

q=22

Explanation:

it will take me a sec to explain hang on

User Shen
by
5.5k points